Self-assembled dendrimer polyamide nanofilms with enhanced effective pore area for ion separation - Bingbing Yuan; Yuhang Zhang; Pengfei Qi; Dongxiao Yang; Ping Hu; Siheng Zhao; Kaili Zhang; Xiaozhuan Zhang; Meng You; Jiabao Cui; Juhui Jiang; Xiangdong Lou; et al. (Nature Communications, 2024)
Abstract Membrane technology using well-defined pore structure can achieve high ion purity and recovery. However, fine-tuning the inner pore structure of the separation nanofilm to be uniform and enhance the effective pore area is still challenging. Here, we report dendrimers with different peripheral groups that preferentially self-assemble in aqueous-phase amine solution to facilitate the formation of polyamide nanofilms with a well-defined effective pore range and uniform pore structure. The high permeabilities are maintained by forming asymmetric hollow nanostripe nanofilms, and their well-designed ion effective separation pore ranges show an enhancement, rationalized by molecular simulation. The self-assembled dendrimer polyamide membrane provides Cl–/SO4 2– selectivity more than 17 times that of its pristine polyamide counterparts, increasing from 167.9 to 2883.0. Furthermore, the designed membranes achieve higher Li purity and Li recovery compared to current state-of-the-art membranes. Such an approach provides a scalable strategy to fine-tune subnanometre structures in ion separation nanofilms.